The effects of organizational culture and organizational communication on lecturer performance - Salim Aktar; Bahdin Nur Tanjung; Elfrianto Elfrianto; Sabar LT Simatupang (Indonesian Journal Education, 2026)
This study aimed to examine the direct effects of organizational culture and organizational communication on the performance of lecturers in private higher education institutions offering Midwifery Study Programs in North Sumatra, Indonesia. A survey method with a path analysis approach was employed to analyze the relationships among the research variables. The study involved 172 lecturers, selected from a population of 310 permanent lecturers using the Isaac and Michael sampling formula. Data on organizational culture and organizational communication were collected using Likert-scale questionnaires, while lecturer performance was assessed through direct observation. The findings revealed that organizational culture had a positive direct effect on lecturer performance (p = 0.222), with innovation and risk-taking representing the strongest contributing dimension. Organizational communication also had a positive direct effect on lecturer performance (p = 0.181), with the relationship dimension providing the greatest contribution. These findings indicate that strengthening organizational culture through innovation and fostering effective organizational communication through positive interpersonal relationships can improve lecturer performance in private higher education institutions.